(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Ovrutsky A.V. Keywords: communicative phenomena, consumer society, commodification, reconsumption information, ‘brandizm’, prosumer, decollectivization, synthesis of information, convergence journalism, zapping. The article analyzes the specific communicative phenomena of the consumer society. They are: commodification, reconsumption information, a new type of consumer, ‘brandizm’, dominant comfort in the information process, decollectivization of information consumption and the creation of synthetic information products. We show that these phenomena are universal and they can characterize the socio-economic system as a whole. The actual phenomenon of journalism, i.e. its commercialization, convergence journalism and zapping are studied in the article.